Gullain‐Barré syndrome following off‐pump coronary artery bypass grafting. Issue 9 (5th August 2018) - Kumar, Vikas; Puri, Deepak; Negi, Sunder; Rahi, Sushil K.; Goswami, Devant
Abstract: We report a case of Gullain‐Barré syndrome after off‐pump coronary artery bypass grafting surgery in a diabetic male with idiopathic thrombocytopenic purpura who recovered fully after treatment with intravenous immunoglobulin without any residual weakness.